Fuzzy Logic for Sensory Evaluation of Paper Sweet (Pootharekulu) - Sivamma, P.; Rao, P. V. K. Jagannadha (International Journal of Bio-resource and Stress Management, 2023)
The present study was conducted at Atreypuramu, East Godavari district, Andhra Pradesh, India during June-August, 2022 with the preparation of paper sweet variants followed by fuzzy logic sensory analysis. Initially, polished/milled Jaya variety rice soaked, ground with water and made into batter. The batter without any coarse particles diluted in separate flat containers. Then, a thin cotton cloth was dipped in the diluted batter and spread over the hot curved surface of inverted pot almost maintained at 120–135°C. This structures the paper-thin external front of the sweet. The size of produced rice starch edible film was about 41×30 cm2 and thickness in the range of 0.02–0.05 cm. The four paper sweet variants were prepared by rolling the rice starch film stuffed with various fillings including jaggery/sugar and nuts & jaggery/sugar alone. Fuzzy logic sensory study was conducted for analysis of paper sweets and to compare the acceptability of these paper sweet variants. Ranking was assigned to each sample by calculating fuzzy membership unction, normalized fuzzy membership function, normalized fuzzy membership function matrix, judgment membership function matrix, judgment subset and quality ranking subset. Finally, the weightage average was compared with quality ranking of all paper sweet variants. The results concluded that all four samples were quite comparable; however, paper sweet with jaggery and nuts received the best response.